Aggressive unicystic ameloblastoma affecting the posterior mandible: late diagnosis during orthodontic treatment - Pereira de Castro Lopes, Sergio Lucio [UNESP]; Flores, Isadora Luana; Gamba, Thiago de Oliveira; Ferreira-Santos, Rivea Ines; Leonelli de Moraes, Mari Eli [UNESP]; Cabello, Aline Alvarez [UNESP]; Moutinho, Paula Nascimento [UNESP] (Korean Acad Oral & Maxillofacial Surgery, 2017)
Maxillofacial images must be examined to find pathologies not identified during clinical examination. Unicystic ameloblastoma (UA) extending to the mandibular body and ramus was neglected on initial panoramic radiographic examination. After orthodontic therapy, a huge lesion was observed clinically and through imaging exams. After the conservative surgery, no recurrence was observed during five years of follow-up. This case emphasized the need for careful evaluation of patient images focusing on the oral diagnosis before any dental treatment planning, including orthodontic therapy.
Keywords: Oral diagnosis; Dentistry; Diagnostic imaging; Ameloblastoma